Budaya Masyarakat NTT dan Citra Peran Perempuan (Sebuah Pendekatan Antropologis) - Gregor Neonbasu SVD; Syahrun Syahrun (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
Women play a central role in the lives of people worldwide. This article aims to explore the female figure from the perspective of East Nusa Southeast society, through a process of cultural reflection and analysis. Research results (2011, 2015) guide the pattern and strategy of this article, supplemented by discussions between the two authors from different backgrounds. The two authors reached a consensus to employ an anthropological approach in their joint study and reflection on the writing topic. The strong influence of culture or tradition on the perception of women's roles and functions is critical to the narrative. When confronted with the diverse advancements brought about by globalization, a range of reactions, both positive and negative, seem to emerge. This article's focus and objective is a practical effort to empower women's roles and functions in accordance with their social potential. In this way, women can actively participate in all activities related to the development of society, nusa, and nation.